Rancang Bangun Mesin Pengaduk dan Pencetak Adonan Keripik Kemplang untuk Skala Industri Rumah Tangga - Rizky Saputra; Bayu Wiro Karuniawan; Tri Tiyasmihadi (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
Kemplang chips are one of the typical snacks from Tuban district. The process of makin kemplang chips based on a surveyof the home industry still uses manual methods. To increase production yields and facilitatethe production process from kemplang chips, new tools or machines are needed that can work efficiently by considering the effectiveness of its working mechanism, so as to make the kemplang chips dough from the mixing to molding process. The method used in this research is the design method. This design is assisted with CAD (Computer Aided Design) software for design making, after the making design and then fabricating the machine components, after fabricating and the assembling the components of the machine. To find out the results of the production of the mixing and molding dough the kemplang chips, a trial was carried out. Based on the results of planning and design that has been done. The dimensions of the mixer and molding machine are produced with the main dimension of 1200 mm x 400 mm x 400 mm. The mixer container is designed to be able to mixer 5 kg/process. For molding machine has designed with 2 dies type, namely with a diameter 5 mm and diameter 25 mm. This machine uses 2 motors, namely 0,5 Pk engine for mixer machine and 1 Pk engine for molding machine.